PENYUSUNAN STANDAR PROSEDUR OPERASI PRODUKSI BERDASARKAN CPPB-IRT DAN WISE PADA INDUSTRI RUMAH TANGGA ANEKA SNACK 3E - Elsa Ayu Lestari; Totok Pujianto; Roni Kastaman (Jurnal Teknologi Industri Pertanian, 2022)
Quality is one of many important aspects that need to be improved and maintained to make sure manufacturers have competitive advantage to meet consumer’s needs. Aneka Snack 3E as a home industry that produces banana and onion chips needs to improve and keep the product quality to be able to compete with other competitors. However, quality control system at Aneka Snack 3E was uncontrolled because the company did not have Standart Operating Procedure (SOP). This research conducted to arrange and implement production’s SOP which include alternative solution from quality improvement of Aneka Snack 3E. The SOP was arranged based on CPPB-IRT (Cara Produksi Pangan yang Baik untuk Industri Rumah Tangga) and WISE (Work Improvement in Small Enterprises) with DMAIC (Define, Measure, Analyze, Improve and Control) cycle as continuous quality improvement method to solve problems to the root. This research identified 31 deviations within production process to CPPB-IRT and Wise. Each causes of those deviations were analyzed and resulting 33 documents to solve the problems. Those documents contain 12 work procedures, 13 work instructions, and 8 forms. The evaluation results show that of the 33 documents made, as many as 18 documents or 55% of documents are considered very applicable and as many as 15 documents or 45% of documents are considered applicable to the Aneka Snack 3E production process. Based on these, with permission of Aneka Snack 3E’s owner, those documents is set to become production’s SOP that needed to be supervised and implemented by Aneka Snack 3E.Keywords: cara produksi pangan yang baik untuk industri rumah tangga, standard operational procedure, quality,work improvement in small enterprises.